THE EFFECT OF BRAND AMBASSADORS, ONLINE CUSTOMER REVIEWS AND PRODUCT QUALITY ON LOCAL SHOES BRAND IMAGE - Siti Amelia; Taufik Hadi Kusumah; May Dedu; Agustina (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
The tremendous growth of the regional footwear industry in Indonesia is increasing consumer interest in home-made goods. Ventela is a well-known brand that can compete in the domestic market and overseas. The purpose of this study is to examine how the brand image of local Ventela shoes is influenced by brand ambassadors, online customer reviews, and product quality. Quantitative research using a survey approach was the methodology used. A questionnaire approach was used to collect data, and multiple linear regression analysis was used for analysis. The study findings show that brand image is significantly influenced by the three independent variables. By working with famous actors and artists who have a large fan base, brand ambassadors help increase customer trust. Consumer perceptions of product quality and longevity are influenced by online user reviews. The main element affecting consumer happiness and loyalty to the Ventela brand is product quality. The competitiveness of local products in the global market and brand image can be improved by marketing methods centered on product quality, online customer reviews, and brand ambassadors.